Wild speculations on the missing flight MH370: balancing online expression and content regulation in Malaysia - Daud, Mahyuddin (LexisNexis Malaysia, 2015)
A recent incident on the disappearance of Malaysia Airlines (MAS) flight MH370 has broken the hearts of people around the world. Joint international investigations have confirmed that the flight ended in the middle of the South Indian Ocean. However, till the day this work is written, no sign of wreckage, dead bodies or any shred of evidence could be found to provide an answer, thus inviting wild speculations to the incident. Wild speculations on plane hijacking, suicide, terrorism acts and more can easily be found online despite warnings by the authorities not to speculate. In this regard, the author recalls the right to freedom of expression (FOE) â which has been long recognised by international treaties. Accordingly, FOE has been expanded to include online expressions. New technology allows Internet content to be created without the need for approval from an editor â like in print media. This could invite the creation of problematic content (such as speculations on MH370) and often leads to intermediary liability of webmasters and service providers. Therefore, this paper seeks to address three significant points. Firstly, a brief problem statement on the MH370 incident and surrounding legal risks caused by wild speculations shall be addressed. Secondly, the author will discuss current legal positions on digital right to FOE vis-a-vis Internet content regulation in Malaysia focusing on online speculations. Finally, the author will provide suggestions to balance between rights to digital expression and Internet content regulation with the view on minimising online risks to netizens.